Analyzing The Influence Of School Climate And Work Motivation On Teacher Performance In Public High School 7 Binjai - Warningsih, Sri; Purba, Sukarman (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to analyze the influence of school climate and work motivation on teacher performance at SMA Negeri 7 Binjai. The research is grounded in the critical role of teacher performance as a measure of professionalism in the implementation of the Merdeka Curriculum, alongside organizational challenges that hinder optimal teaching quality. A quantitative approach with correlational design and multiple linear regression analysis was employed. The research involved all 40 teachers at SMA Negeri 7 Binjai as the sample, using a total sampling technique. Data were collected through a closed-ended questionnaire consisting of 57 validated and reliable items. The results showed that both school climate and work motivation significantly influence teacher performance, both partially and simultaneously. Individually, school climate accounted for 29.4% of the performance variance, while work motivation contributed 49.7%; together, both variables explained 55.7% of the variance. These findings underscore the importance of building a supportive work environment and enhancing teacher motivation through comprehensive managerial strategies. The study offers practical implications for school leaders, education managers, and policymakers in designing effective, collaborative, and sustainable interventions to improve teacher performance and educational quality in secondary schools.